Calibrating a stochastic SIR-model to simulated data using different calibration methods : a tutorial & comparison of methods - Van Staden, Wynand-Junior (Stellenbosch : Stellenbosch University., 2020)
Thesis (MSc)--Stellenbosch University, 2020.